ETV6-NTRK3 Is Expressed in a Subset of ALK-Negative Inflammatory Myofibroblastic Tumors. (August 2016) - Alassiri, Ali H.; Ali, Rola H.; Shen, Yaoqing; Lum, Amy; Strahlendorf, Caron; Deyell, Rebecca; Rassekh, Rod; Sorensen, Poul H.; Laskin, Janessa; Marra, Marco; Yip, Stephen; Lee, Cheng-Han; et al.
Abstract : Inflammatory myofibroblastic tumor (IMT) is a genetically heterogenous tumor of the viscera and soft tissues, with multiple molecular features having been demonstrated in this tumor type. About 50% of cases harbor an anaplastic lymphoma kinase ( ALK ) gene rearrangement, and recent studies have described novel fusions involving the ROS1 and PDGFRβ genes in a subset of ALK-negative cases. However, the molecular features of the remaining subset of cases are not yet defined. We report a case of a large, highly aggressive IMT of the lung in a 17-year-old girl. This case was molecularly characterized through whole-genome and transcriptome sequencing. Subsequently, we investigated a cohort of 15 ALK-negative IMTs of various anatomic sites. All cases were screened using fluorescence in situ hybridization (FISH) for rearrangement of the ETV6 locus and with reverse transcription polymerase chain reaction (RT - PCR) for the ETV6-NTRK3 fusion transcript. Whole-genome and transcriptome sequencing revealed an ETV6-NTRK3 fusion transcript in our index case. This was confirmed by FISH studies for ETV6 gene rearrangement, as well as by RT-PCR. In addition, 2 additional cases in our cohort demonstrated ETV6 rearrangement by FISH. The presence of ETV6-NTRK3 fusion transcript was demonstrated by RT-PCR in one of these additional cases. In summary, we demonstrate the expression of the ETV6-NTRK3 fusion oncogene in a small subset of IMTs, lending further support to the role of oncogenic tyrosine kinases in the pathophysiology of this tumor type. Our data also further expand the growing spectrum of tumor types expressing the ETV6-NTRK3 fusion. Abstract : Supplemental Digital Content is available in the text.